Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How to prove that $(1 + x)^\frac{1}{b}$ (where $b$ is an integer) can be expressed as a formal power series without using Binomial theorem?

share|improve this question
add comment

5 Answers 5

up vote 10 down vote accepted

The coefficient recurrence arises from the obvious first-order differential equation, namely

$$\rm\ \frac{y'}y\ =\ (log\ y)'\:=\ \bigg(\frac{log(1+x)}b\bigg)'\:=\ \frac{1}{b\ (1+x)}\ \ \ \Rightarrow\ \ \ y\: =\ b\ (1+x)\ y'$$

Therefore $\displaystyle\rm\ \ y\ =\ \sum_{k\ge 0}\ a_k x^k\ =\ b\ (1+x)\ \sum_{k\ge 0}\ (k+1)\ a_{k+1}\ x^k\:,\ \: $ which, after algebra, yields

$$\rm a_{k+1}\ =\ \frac{1-b\:k}{b\:(k+1)}\ a_k,\ \ \ a_0 = 1$$

As a check, note that it yields the binomial formula for $\rm\ b = 1/n,\ y = (1+x)^n\ $ since then

$$\rm \frac{a_{k+1}}{a_k}\ =\ \frac{n-k}{k+1}\ =\ \frac{n\choose k+1\:}{n\choose k\:}$$

and $\rm\ a_k = 0\ $ for $\rm\ k > n\ $ since the above implies $\rm\ a_{n+1} = 0\ $ hence $\rm\ a_{n+i} = 0\ $ for all $\rm\:i>0\:.$

share|improve this answer
1  
+ 1 Nice, can I use this technique to prove the Generalize Binomial Theorem? –  Mark May 13 '11 at 21:34
    
Update: It works –  Mark May 13 '11 at 23:23
add comment

We can use Newton's method to find a root to the function

$$ g(t) = t^b - (1+x) $$

by using the iteration

$$t_{n+1} = t_n - \frac{g(t_n)}{g'(t_n)} = t_n - \frac{t_n^b - (1+x)}{b t_n^{b-1}} $$

We can see this converges by observing that if the reciprocal of $t_n$ is a formal power series (i.e. its leading coefficient is nonzero) and we have

$$ g(t_n) \equiv 0 \pmod{x^k} $$

then we must also have have

$$ t_{n+1} \equiv t_n \pmod{x^k} $$

and the Taylor series formula gives

$$ \begin{align*}g(t_{n+1}) &= g(t_n) - g'(t_n) \frac{g(t_n)}{g'(t_n)} \mod{\left(\frac{g(t_n)}{g'(t_n)}\right)^2} \\ &=0 \mod x^{2k} \end{align*} $$

If we set $t_0 = 1$, then it's easy to check that

$$g(t_0) \equiv 0 \pmod x \qquad \qquad t_n \equiv 1 \pmod x $$

and thus the limit of this sequence is a formal power series that is a root of $g(t)$.

share|improve this answer
add comment

We do it for $b>0$. A similar argument will work for $b<0$. Note that the argument is purely formal.

So we are trying to find $a_0$, $a_1$, $a_2$, and so on such that $$1+x=(a_0+a_1x+a_2x^2+ \cdots +a_nx^n +\cdots)^b$$ where equality is meant in the formal sense. It is clear that we want $a_0=1$ and $a_1=1/b$.

There is a natural proof by induction, if we choose the induction hypothesis correctly.
Let $n \ge 1$. Assume by way of induction hypothesis that there are numbers $a_0, a_1, \dots, a_n$ such that $$(a_0+a_1x+\cdots+a_nx^n)^b$$ formally agrees with $1+x$ in positions $0, 1,\dots,n$. We will show that we can choose $a_{n+1}$ such that
$$(a_0+a_1x+\cdots+a_{n+1}x^{n+1})^b$$ formally agrees with $1+x$ in positions $0, 1,\dots,n+1$.

That is easy. Let $c_{n+1}$ be the coefficient of $x^{n+1}$ in $(a_0+a_1x+ \cdots +a_nx^n)^b$. Define $a_{n+1}$ by $ba_{n+1}=-c_{n+1}$.

share|improve this answer
add comment

We are looking for a power series $f=1+a_1x+a_2x^2+\cdots$ such that $f^b=1+x$. Writing out $f^b$, you get $1+ba_1x+g_2(a_1,a_2)x^2+g_3(a_1,a_2,a_3)x^3+\cdots$, where $g_i(a_1,a_2,\ldots,a_i)$ is a linear function of the coefficients. Then for $f^b=1+x$, we need to solve a system of equations $$ba_1=1$$ $$g_2(a_1,a_2)=0$$ $$g_3(a_1,a_2,a_3)=0$$ $$\vdots$$ This gives us an infinite system of equations which can be solved iteratively, starting with $a_1=1/b$.

share|improve this answer
    
+1 But is it possible to find the exact series? –  Mark May 13 '11 at 19:56
    
@Mark: Looks like @user6312 made this argument explicit. –  Grumpy Parsnip May 13 '11 at 20:22
add comment

I don't think you mean it is (literally) a formal power series, because it isn't. It can be expressed as a formal power series (in $x$), because it is an analytic function of $x$ in a neighbourhood of $x=0$. You could use the Inverse Function Theorem for that.

share|improve this answer
    
Since this is a special case of Generalize Binomial theorem (GBT) I suppose giving a proof of the Generalize binomial theorem would suffice? Also could one prove GBT using Inverse Function Theorem? –  Mark May 13 '11 at 19:49
3  
Do you think that $\rm\:2^b\:$ is (literally) an integer? –  Bill Dubuque May 14 '11 at 7:41
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.